'Choosing Wisely' culture among Brazilian cardiologists. (1st March 2018) - Correia, Luis C L; Barcellos, Guilherme B; Calixto, Vitor; Volschan, André; Barreto-Filho, José A S; Lopes, Renato D; Rassi, Anis; Levinson, Wendy; de Paola, Angelo A V
Abstract: Objective: (i) To describe how aligned the 'Choosing Wisely' concept is with the medical culture among Brazilian cardiologists and (ii) to identify predictors for physicians' preference for avoiding wasteful care. Design: Cross-sectional study. Setting: Brazilian Society of Cardiology. Participants: Cardiologists who agree to fill a web questionary. Intervention: A task force of 12 Brazilian cardiologists prepared a list of 13 'do not do' recommendations, which were made available on the Brazilian Society of Cardiology website for affiliates to assign a supported score of 1 to 10 to each recommendation. Main Outcome Measurement: Score average for supporting recommendations. Results: Of 14 579 Brazilian cardiologists, 621 (4.3%) answered the questionnaire. The top recommendation was 'do not perform routine percutaneous coronary intervention in asymptomatic individuals' (mean score = 8.0 ± 2.9) while the one with the lowest support was 'do not use an intra-aortic balloon pump in infarction with cardiogenic shock' (5.8 ± 3.2). None of the 13 recommendations presented a mean grade >9 (strong support); 7 recommendations averaged 7–8 (moderate support) followed by 6 recommendations with an average of 5–7 (modest support). Multivariate analysis independently identified predictors of the score attributed to the top recommendation; being an interventionist and time since graduation were both negatively associated with support. Conclusions: (i) The support of Brazilian cardiologists for the 'Choosing Wisely' concept is modest to moderate, and (ii) older generations and enthusiasm towards the procedure one performs may be factors against the 'Choosing Wisely' philosophy.